Efektivitas Iklan Youtube Tolak Angin Versi Ramadhan 1445 H Menggunakan Epic Model pada Masyarakat Kota Semarang - Muhamad Raihan Pradipta Putra; Urip Mulyadi (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study evaluated the effectiveness of the Ramadan 1445 H edition of YouTube Tolak Angin advertising in Semarang City using the EPIC Model (Empathy, Persuasion, Impact, Communication). Using a descriptive quantitative method, data were collected from 100 respondents through an online questionnaire and analyzed with a partial T test in SPSS 27. The results showed effective advertising with an average EPIC score of 3.92, where all dimensions had a positive and significant effect, especially Communication. Based on the S-O-R theory, advertising triggers consumer empathy and confidence, which drives purchase intent, information searching, and increased brand awareness.